Short-term herbivory has long-term consequences in warmed and ambient high Arctic tundra - Chelsea J Little; Helen Cutting; Juha Alatalo; Elisabeth J Cooper (Environmental Research Letters, 2017)
Climate change is occurring across the world, with effects varying by ecosystem and region but already occurring quickly in high-latitude and high-altitude regions. Biotic interactions are important in determining ecosystem response to such changes, but few studies have been long-term in nature, especially in the High Arctic. Mesic tundra plots on Svalbard, Norway, were subjected to grazing at two different intensities by captive Barnacle geese from 2003–2005, in a factorial design with warming by Open Top Chambers. Warming manipulations were continued through 2014, when we measured vegetation structure and composition as well as growth and reproduction of three dominant species in the mesic meadow. Significantly more dead vascular plant material was found in warmed compared to ambient plots, regardless of grazing history, but in contrast to many short-term experiments no difference in the amount of living material was found. This has strong implications for nutrient and carbon cycling and could feed back into community productivity. Dominant species showed increased flowering in warmed plots, especially in those plots where grazing had been applied. However, this added sexual reproduction did not translate to substantial shifts in vegetative cover. Forbs and rushes increased slightly in warmed plots regardless of grazing, while the dominant shrub, Salix polaris , generally declined with effects dependent on grazing, and the evergreen shrub Dryas octopetala declined with previous intensive grazing . There were no treatment effects on community diversity or evenness. Thus despite no changes in total live abundance, a typical short-term response to environmental conditions, we found pronounced changes in dead biomass indicating that tundra ecosystem processes respond to medium- to long-term changes in conditions caused by 12 seasons of summer warming. We suggest that while high arctic tundra plant communities are fairly resistant to current levels of climate warming, underlying ecosystem processes are beginning to change. In addition, even short bouts of intense herbivory can have long-term consequences for some species in these communities.